Effect of Pseudomonas fluorescens (IISR-6) and Trichoderma harzianum (P-26) on growth of black pepper (Piper nigrum L.) in the nursery - Anandaraj, C K Thankamani, K Sreekala, M (Journal of Spices and Aromatic Crops, 2005)
Experiments conducted to study the effect of Pseudomonas fluorescens (IISR-6) and Trichoderma harzinaum (P-26) on growth of black pepper (Piper nigrum) rooted cuttings in the nursery indicated that maximum height and leaf area of cuttings were obtained with application of P. fluorescens thrice, which was on par with raising cuttings in T. harzianum applied potting mixture and application of P. fluorescens thrice. Number of roots and biomass production were higher with combined application of P. fluorescens (thrice) and T. harzianum which was on par with application of P. fluorescens thrice.